Chromosome evaluation of southern South American species of Camptosema and allied genera (Diocleinae - Phaseoleae - Papilionoideae - Leguminosae) - Sede, S.M. (2006)
The genera Camptosema, Galactia and Collaea are grouped in a complex with exomorphological similarities and different criteria have been adopted to circumscribe them. The neotropical genus Camptosema in its southern distribution is represented by four species of which only the type, C. rubicundum, shows the diagnostic features of the genus. The other three taxa, C. paraguariense, C. praeandinum and C. scarlatinum are related morphologically to Camptosema s.s., Galactia and Collaea. In the subtribe Diocleinae, Camptosema is characterized by n = 11 chromosomes and Galactia and Collaea by n = 10. The aim of this study was to analyse cytological characters with special emphasis on the species of uncertain taxonomy. The most relevant character is chromosome number, which in the conflicting species of Camptosema is the same as in Galactia and Collaea. In this paper the chromosome numbers of C. praeandinum (2n = 20), C. paraguariense (n = 10) and C. scarlatinum (n = 10) are reported for the first time. These results, together with the morphological affinity and the phylogenetic hypotheses of other authors, would be of use for revising the current circumscription of these species. © 2006 The Linnean Society of London.